PENINGKATAN KINERJA PEGAWAI PELAYANAN KELURAHAN POTROBANGSAN MAGELANG DI ERA ADAPTASI KEBIASAAN BARU PANDEMI COVID-19 - Sugeng; Muhammad Mathori (Jurnal Riset Mahasiswa, 2023)
The purpose of this study was to analyze the causes of the improvement in the performance of the service employees of the Potrobangsan Magelang village in the era of adaptation to the new habits of the Covid-19 pandemic, to formulate efforts to improve the performance of the service employees of the Potrobangsan Magelang village in the era of adaptation to the new habits of the Covid-19 pandemic. This writing uses a descriptive qualitative method. The subjects in this study were informants who provided information in this study as many as 3 people consisting of 1 Head of Governance Section, 1 Government Administrator, and 1 Potrobangsan Village Integrated Service Personnel (PATEN). Data analysis uses an interactive model by Miles and Huberman (1992) which includes four components, namely data collection, data reduction, data presentation, conclusion drawing or verification. The result is an increase in the performance of service employees at the Potrobangsan Magelang Village in the Adaptation Era to the New Habits of the Covid-19 Pandemic. The reasons include, among others, the number of service employees who are still lacking, the ability of employees in information technology is still low, and infrastructure facilities are not fully fulfilled and according to standards. Efforts were made to improve the performance of service employees in the Potrobangsan Magelang Village in the Era of Adaptation to New Habits of the Covid-19 Pandemic, immediately following up with a meeting with all employees regarding service delivery by emphasizing commitment, making Service Declarations, improving Service Standard Operating Procedures (SOP), monitoring and evaluation. periodically on the implementation of SOPs, capacity building of public service employees through education and training on excellent service, and the need for coordination with agencies in charge of public services and improvement of service facilities and infrastructure.